Effect of silicon carbide particle size on microstructure and properties of a coating layer on steel produced by TIG technique. Issue 4 (1st October 2016) - Muñoz-Escalona, P.; Mridha, S.; Baker, T. N.
Abstract: Surface engineering is essential to prolong life of engineering components subjected to deterioration in service from wear, erosion or corrosion, separately or in combination. This is possible by, for example, incorporating ceramic particles into a molten substrate surface, which may result in the partial or complete dissolution of the particles, and precipitation of a new phase, giving enhanced surface protection. Here, a single-track surface zone of a microalloyed steel was preplaced with a layer of SiC particles 1 and 75 μm in size, melted at a constant heat input with a tungsten inert gas torch using argon as shielding gas. The aim was to compare the melted track without SiC particles and when using SiC particles on the generated temperature, microstructure, melt dimension and hardness of the re-solidified surfaces. Previous work has shown that microstructural changes occur along the track length due to preheating of the un-melted surface ahead of the molten zone. This effect was explored by inserting thermocouples along the 300-mm length of steel. By optimising the process parameters, a re-solidified melt layer free of porosity has been achieved with 75-μm sized SiC particles. This melt reached a maximum hardness of 750 HV.